Bending of a Homogeneous Beam with a Monosymmetric Cross Section – Shear Effect - MAGNUCKI, Krzysztof; MAGNUCKA-BLANDZI, Ewa; WITKOWSKI, Dawid; STEFAŃSKA, Natalia (Engineering Transactions, 2024)
This paper is devoted to the study of a homogeneous clamped beam with a monosymmetric cross section under uniformly distributed load or three-point bending. A nonlinear shear deformation theory of a plane beam cross section based on the classical shear stress formula known as the Zhuravsky shear stress is developed. The values of shear coefficients and maximum deflections of exemplary beams are analytically determined. Moreover, numerical FEM computations for these beams are carried out. The results of the research from both methods are shown in figures, specified in tables, and compared. The percentage relative differences between the analytical and numerical results prove that the proposed original shear deformation theory accurately describes the shear deformation problem of a beam’s planar cross‑section.